Design of a bipolar Dickson voltage multiplier suitable for low output voltage conditions to provide efficient food processing - Daigo Nakashima; Yoshiki Kino; Kei Eguchi (Energy Reports, 2023)
There has been a growing demand for soft and nutritious foods in recent years. However, general food processing applies heat to food, which destroys nutrients in it. For this reason, many researchers have devised several non-thermal food processing methods so far. However, these methods have potential for improvement in terms of manufacturing cost and processing time. Thereby, we proposed the Dickson voltage multiplier which has bipolar topology suitable for low output voltage conditions in order to provide efficient food processing with low cost. The system is equipped with a high-speed driver using IGBTs, which allows the high-voltage multiplier to operate at high speed. In addition, by using Dickson multiplier with a bipolar topology, the voltage stress on each circuit component is reduced. Furthermore, we performed theoretical analysis to calculate the internal resistance and voltage gain of proposed multiplier. Moreover, we confirmed experimentally the possibility of the proposed multiplier by using the prototype.